A holistic approach proposal for 3D underground land management (3D ULA) in Turkey: The case of utility network - Surmeneli, Hicret Gursoy; Sun, Jing; Alkan, Mehmet (WILEY, 2024)
Physical and cadastral data management practices for underground facilities are insufficient to represent underground assets' Rights, Restrictions, and Responsibilities (RRRs) and their relationships with the cadastre. For this reason, developing a 3D integrated data (underground and above-ground) model may be an approach to an effective land management system. This research aims to develop a creative data model by integrating Turkish National Geographic Information System (TUCBS-AY in Turkish) with international standards (Land Administration Domain Model (LADM) and CityGML) as a holistic approach. The requirements determined for underground facilities using TUCBS-AY were used. Since the data produced in Turkey were modeled according to the CityGML 2.0 version, the CityGML 2.0 UtilityNetwork version was used in the study to be compatible with the existing Turkish cadastral system. While some classes in the model are generalized, they are expanded using LADM's classes for legal rights and part information. In addition, the CityGML classes have been expanded within the model so that parcels, buildings, and independent sections are represented separately, thus providing the opportunity to represent the underground utilities associated with them, their RRRs, and ownership situations. Requirements for the proposed model were determined based on Turkey's cadastral system and underground data. The main purpose is to manage the legal and physical relations of underground and surface objects at the city scale, compatible with the current Turkish cadastral system, with a holistic approach. The proposed integrated conceptual data model shows how legal rights and ownership of underground structures can be logically represented with a 3D data model.
Keywords: CADASTRE; CITYGML; OBJECTS; Geography